2023
DOI: 10.3390/cancers15030839
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Robot-Assisted Surgery in Rectal Cancer Compared with Open and Laparoscopic Surgery

Abstract: With increasing trends for the adoption of robotic surgery, many centers are considering changing their practices from open or laparoscopic to robot-assisted surgery for rectal cancer. We compared the outcomes of robot-assisted rectal resection with those of open and laparoscopic surgery. We searched Medline, Web of Science, and CENTRAL databases until October 2022. All randomized controlled trials (RCTs) and prospective studies comparing robotic surgery with open or laparoscopic rectal resection were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…A large meta-analysis by Khajeh et al showed that robotic surgery had better outcomes than the laparoscopic approach in terms of bleeding, the need for reoperation, and complete tumor resection. 8 Robotic rectal resection has a low rate of positive circumferential resection margins, a high rate of appropriate total mesorectal excision, and good overall and disease-free survival. 9 Even when focusing on abdominoperineal resection, robotic surgery has demonstrated better short-term outcomes than laparoscopic surgery, suggesting that it could be a useful approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large meta-analysis by Khajeh et al showed that robotic surgery had better outcomes than the laparoscopic approach in terms of bleeding, the need for reoperation, and complete tumor resection. 8 Robotic rectal resection has a low rate of positive circumferential resection margins, a high rate of appropriate total mesorectal excision, and good overall and disease-free survival. 9 Even when focusing on abdominoperineal resection, robotic surgery has demonstrated better short-term outcomes than laparoscopic surgery, suggesting that it could be a useful approach.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have supported the safety and efficacy of robotic surgery for rectal cancer. A large meta‐analysis by Khajeh et al showed that robotic surgery had better outcomes than the laparoscopic approach in terms of bleeding, the need for reoperation, and complete tumor resection 8 . Robotic rectal resection has a low rate of positive circumferential resection margins, a high rate of appropriate total mesorectal excision, and good overall and disease‐free survival 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Open resection was associated with a higher rate of surgical site infection compared to the robotic approach without a difference in leak rate. Oncologic resection was superior in the robotic approach, which had a higher rate of R0 resections ( p = 0.04), negative circumferential resection margin ( p = 0.03), and number of LN examined ( p = 0.02); however, there was no difference in DFS or OS 121 …”
Section: Colorectal Surgerymentioning
confidence: 97%
“…Oncologic resection was superior in the robotic approach, which had a higher rate of R0 resections (p = 0.04), negative circumferential resection margin (p = 0.03), and number of LN examined (p = 0.02); however, there was no difference in DFS or OS. 121…”
Section: Robotic Versus Open Colorectal Surgerymentioning
confidence: 99%
“…[6][7][8] Although many articles have been published on the comparison of early and middle rectal cancer. [9][10][11] There are few studies on locally advanced rectal cancer. [10] The treatment plan and results of the 2 stages of rectal cancer are significantly different.…”
Section: Introductionmentioning
confidence: 99%